As formações superficiais do Chapadão do Diamante - Serra da Canastra: contributos geoquímicos, físicos e geocronológicos - Santos, Fabiana Cristina dos (2021)
This research aims to understand how the geochemical processes act in the elaboration of the relief forms of the Chapadão do Diamante in the Serra da Canastra National Park-MG and contribute to the understanding of the spatial distribution of chemical and physical attributes integrated to the geochronological ones. To this end, a geochronological sketch map containing the ages of the deposit materials, chemical and physical analyses of the surface materials, and the statistical treatment of the geochemical data were made to recognize the main components and their groupings, as well as their spatialization. Quartzite weathering in the studied region consists of the dissolution of the quartz along with the crystal arrangement. Thus the quartzite loses cohesion and is reduced to sand. In the subsurface weathering occurs preferentially in the stratification planes. The geochemical emptying is then able to disaggregate the quartzite. This fact, together with the subsurface weathering, promotes the lowering of the relief, forming flattened surfaces. The leaching of silica occurs in alteration mantles at advanced stages of weathering, providing the formation of iron and aluminum oxides and hydroxides, when in sufficient quantities, can lead to laterization processes. Laterization and intense leaching have favored the formation of goethite, hematite, and gibbsite, elements that suggest that the area has long been under the influence of a hot and humid climate. These same elements favor the translocation of organic matter in materials where the source material is poor in clay. The union of the geochemical processes leads to a generalized loss of a large part of all the elements found, except for those of low mobility such as aluminum and iron. These facts suggest that the Chapadão do Diamante presents an expressive geochemical emptying at present, meaning a progressive loss of volume, manifested more intensely in the weathering layers, as can be observed in each relief form analyzed.